Literatur Review: Pengaruh Audit Kinerja terhadap Akuntabilitas Publik dengan Pengawasan Fungsional sebagai Moderator - Auliya Siwi Nugrahani (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
A performance audit is an audit activity systematically and objectively based on the type of evidence to assess the efficiency, effectiveness, and economics of the audited entity's operations to improve unit operations and achieve good public accountability. This research aims to get to know more about how much influence public sector audit performance has on public accountability through functional oversight that acts as a moderator. This research is a qualitative research type, in which public sector organizations are the object of the research being studied. Conducting research methods in the form of a literature review by analyzing books and scientific writings that have the same title and discussion, so that there are 3 journals taken randomly. This study found that there is a significance between Performance Audits on Public Accountability and Functional Supervision in moderating performance audits on Public Accountability.